TOKOH UTAMA WANITA DALAM NOVEL GENRE ROMAN INDONESIA (PERIODE 1970-an & 1980-an) - Malik, Elmy Selfiana (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2022)
The year of 1970s and 1980s was an important period in the history of the growth and development of the romance genre novel in Indonesia. During this period, many romance novels were published, especially by female authors. The romance genre is a genre that describes the love story between the main characters, male and female. The main female character in the novel is one of the important aspects in the formulation of a romance story. Therefore, this study aims to determine the characteristic of the main female characters in Indonesian romance novels in the 1970s and 1980s. The method used in this research is the descriptive qualitative method. The result of this study is that the characteristics of the main female characters featured in romance novels in the 1980s are more varied compared to the characteristics of the main female characters in the 1970s. Even though the changes are not too significant, the results of the analysis show that there are slight changes. It can be seen in the physical depiction, profession, and also the role of the main female characters.